‘Faith’ in Funerals? Robust attenuation or terminal decline? Religious and spiritual presences in a post-pandemic funeral landscape - Baker, Christopher (Journal of contemporary religion, 2025)
This article analyses the fluid and rapidly evolving funeral event landscape in the UK with a view to locating the role and presence of faith within these changes. The article draws on recent multi-stranded research which collated the views, perspectives, and experiences of key stakeholders, including funeral arrangers, independent celebrants and those attached to religious institutions, and families living with bereavement. It triangulated these narratives with survey data and an analysis of 1,000 funeral service plans which detailed the choice of music and readings (including religiously based items). This article focuses on the experiences of those on the front line of negotiating the development of new funeral spaces within an ongoing secularly framed milieu, with its increased emphasis on individuation, personalisation, and choice, including the sequestration of the body of the deceased and the disaggregation of funeral costs through the use of specially designed apps. The article identifies and explains how the presence and role of faith in the form of religious and spiritual items in the funeral event, although attenuated compared to the context 25 years ago, remain robustly and consistently present within current practice.